Articular sartilage regeneration with autologous marrow aspirate and hyaluronic acid: an experimental study in a goat model - Mohd Azam Khan Goriman Khan; Khay - Yong Saw; Paisal Hussin; Seng-Cheong Loke (2009)
Purpose